2016
DOI: 10.1073/pnas.1525086113
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthesis is necessary for autoreactive T-cell trafficking, activation, and Th1 polarization

Abstract: The extracellular matrix polysaccharide hyaluronan (HA) accumulates at sites of autoimmune inflammation, including white matter lesions in multiple sclerosis (MS), but its functional importance in pathogenesis is unclear. We have evaluated the impact of 4-methylumbelliferone (4-MU), an oral inhibitor of HA synthesis, on disease progression in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS. Treatment with 4-MU decreases the incidence of EAE, delays its onset, and reduces the severity of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 51 publications
9
68
0
Order By: Relevance
“…We demonstrated recently that 4-MU treatment prevents autoimmune disease in the EAE mouse model of MS [16]. We also examined whether the route of delivery impacted the efficacy of 4-MU in this model.…”
Section: Oral But Not Ip 4-mu Prevents Autoimmunitymentioning
confidence: 99%
See 4 more Smart Citations
“…We demonstrated recently that 4-MU treatment prevents autoimmune disease in the EAE mouse model of MS [16]. We also examined whether the route of delivery impacted the efficacy of 4-MU in this model.…”
Section: Oral But Not Ip 4-mu Prevents Autoimmunitymentioning
confidence: 99%
“…This drug has been shown to inhibit HA production in multiple cell lines and tissue types both in vitro and in vivo [17,[37][38][39][40]. We have reported that 4-MU treatment prevented or reversed autoimmune disease in mouse models of T1D and MS [13,16].…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations